Resolution of MRS applied to the characterization of hard-rock aquifers - Legchenko, Anatoly (Ground water, 2006)
The performance of the Magnetic Resonance Sounding (MRS) method applied to the investigation of heterogeneous hard-rock aquifers was studied. It was shown using both numerical modeling and field measurements that MRS could be applied to the investigation of the weathered part of hard-rock aquifers when the product of the free water content multiplied by the thickness of the aquifer is >0.2 (for example, 10-m-thick layer with a 2% water content). Using a currently available one-dimensional MRS system, the method allows the characterization of two-dimensional subsurface structures with acceptable accuracy when the size of the subsurface anomaly is equal to or greater than the MRS loop. However, the fractured part of hard-rock aquifers characterized by low effective porosity (<0.5%) cannot be resolved using currently available MRS equipment. It was found that shallow water in the weathered part of the aquifer may screen MRS signals from deeper water-saturated layers, thus further reducing the possibility of investigating deeper fractured aquifers. A field study using the NUMIS(plus) MRS system developed by IRIS Instruments was carried out on an experimental watershed in southern India. A heterogeneous unconfined aquifer in a gneissic formation was successfully localized, and MRS results were confirmed by drilling shortly after the geophysical study. The top of the aquifer revealed by MRS was found to be in a good agreement with observed static water level measurements in boreholes